Pengembangan Desain Walker Fleksibel Bagi Lansia - Idiar; Muhammad Yunus (Jurnal Mesin Nusantara, 2021)
The health condition of the elderly generally has decreased which can cause several physical and mental problems. Elderly aged over 70 years or 60 years who have health problems are categorized as high risk elderly. In carrying out their daily activities inside the house or outside the house, such as going to the mosque, garden, etc., they usually use a equipment called a walker. The types of walkers on the market still have limitations, so they need to be developed in a flexible walker design. The stages used in the flexible walker design development research are compiling a list of requirements, determining reference concepts, developing alternative concepts, selecting concepts, and analyzing techniques and postures for the selected design. The selected concept has specifications, namely the front pedestal functions as a fixed leg or wheeled leg, the arm of the walker holder can be adjusted up and down by 150 mm in height, has a seat that can be folded, and the walker can be folded. In addition, the results of stress analysis on the critical component, namely the main fulcrum, obtained safe criteria where the maximum stress value that occurs is 7.35x106 N/m2 is given still below the yield strength value of the brass material 3.5x108 N/m2. Posture analysis using the RULA method in standing and sitting positions obtained an average final score of 2 in the acceptable category for walker users..